2010
DOI: 10.1007/s11738-010-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of lactoalbumin hydrolysate and methyl jasmonate on ginsenoside and polysaccharide production in Panax quinquefolium L. cells cultures

Abstract: Lactoalbumin hydrolysate (LH) at 100 mg L -1 with methyl jasmonate (MJ) at 2 mg L -1 synergistically stimulated ginsenoside accumulation in Panax quinquefolium cells compared with 100 mg L -1 LH. Combination elicitors led to higher ginsenoside productivity (45.93 mg L -1 ) than single treatment of 100 mg L -1 LH (31.37 mg L -1 ). This present result will be helpful in providing a tool for enhancing the productivity of ginsenoside by Panax quinquefolium cell cultures on a commercial scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Thanh et al also found ginsenoside accumulation in ginseng cell cultures was enhanced by elicitation of 200 μM MJ, and the ginsenoside content was two times that of the control [ 25 ]. In the present study, live endophyte not only increased biomass, but also improved ginsenoside accumulation in adventitious root culture, the ginsenoside production was four times that of the control, which was higher than other studies which used MeJA as an elicitor [ 24 , 25 ].…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…Thanh et al also found ginsenoside accumulation in ginseng cell cultures was enhanced by elicitation of 200 μM MJ, and the ginsenoside content was two times that of the control [ 25 ]. In the present study, live endophyte not only increased biomass, but also improved ginsenoside accumulation in adventitious root culture, the ginsenoside production was four times that of the control, which was higher than other studies which used MeJA as an elicitor [ 24 , 25 ].…”
Section: Resultscontrasting
confidence: 64%
“…Therefore, the degree of culture biomass inhibition should be considered before choosing an elicitor. Some studies found that the combination of elicitors increased the accumulation of secondary metabolites, such as 100 mg mL −1 lactoalbumin hydrolysate mixed with 2 mg L −1 MeJA, which enhanced ginsenoside accumulation in Panax quinquefolius cells [ 24 ]. To compare elicitation by MeJA and strain LB 5-3 on adventitious root cultures, MeJA, endophytic bacteria and their combination were added during flask culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, efforts to increase bioactive compounds need to be continued during the culture. MeJA as an elicitor has a good elicitation role in many culture systems [4,[23][24][25][26], including O. elatus AR culture. Jiang et al [4] indicated that MeJA (200 µM) increases bioactive compound production in the batch culture of O. elatus ARs.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic ginseng plants with stable heredity and high saponin content productivity need to be further investigated. Main achievements of ginseng tissue and cell cultures in recent years are summarized in Table 2 92 , 94 , 169 , 173 , 178 , 184 , 186 , 187 , 188 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 .…”
Section: Biotechnological Approaches For Ginsenoside Productionmentioning
confidence: 99%